Permanent military force for united nations : a pragmatic solution to low-intensity conflict? - Cheang, Christy. (2008)
This paper proposed to the united nations to obviate the need for international volunteerism on the part of member states, and to establish a Permanent Military Force, where individuals are recruited from the global market, trained and deployed directly under the united nations.